predictors of long-term fatal cardiovascular events after planned percutaneous coronary interventions - E. O. Vershinina; A. N. Repin (Российский кардиологический журнал)
Aim. To evaluate the frequency and identify predictors of longterm fatal cardiovascular events (CVE) after planned percutaneous coronary interventions (PCI).Material and methods. We conducted a retrospective study that included 150 patients who underwent planned endovascular intervention on the coronary arteries. Outcomes of interventions were assessed 6 years after the PCI, by analyzing medical records and telephone interviews. The primary endpoint of the study was cardiovascularrelated death. Results. Fatal CVE were recorded in 10,6% of patients. A statistically significant relationship was found between the development of fatal CVE in the longterm period after planned PCI and the presence of initial chronic obstructive pulmonary disease in patients (OR=12,3; CI (3,641,5); р<0,001), atrial fibrillation (OR=5,1; CI (1,616,3); p=0,003), diabetes mellitus (OR=3,2; CI (1,19,8); p=0,032), acute cerebrovascular accident (OR=8,6; CI (2,036,4); p=0,001); any clinical complications of interventions (OR=3,1; CI (1,19,0); p=0,028), taking of antiarrhythmic drugs (OR=5,9; CI (1,327,4); p=0,012), statins taking at the time of PCI (OR=0,3; CI (0,10,8); p=0,013). According to the results of the ROCanalysis, the most significant predictor of fatal CVE in the longterm period was erythrocyte sedimentation rate more than 14,5 mm/h (AUC=0,677; CI (0,5070,835); p=0,027). According to 6year observation, KaplanMeier curves showed a significant effect of multifocal atherosclerosis, acute periprocedural kidney injury and heart rhythm disorders recorded during PCI, on the incidence of longterm fatal CVE.Conclusion. A statistically significant relationship between the development of fatal CVE in the longterm period after planned PCI and the presence of initial comorbid pathology in patients (chronic obstructive pulmonary disease, atrial fibrillation, diabetes mellitus, multifocal atherosclerosis, acute cerebrovascular accident), erythrocyte sedimentation rate more than 14,5 mm/h, concomitant drug therapy at the time of the intervention (taking of antiarrhythmic drugs, statins). Significant predictors of adverse longterm outcome after planned endovascular myocardial revascularization were clinical complications of PCI, recorded during the hospital period, especially acute periprocedural kidney injury and heart rhythm disorders.